The Harmony of Education and Upbringing as a Key Factor in Forming a Well-Rounded Individual - Muradova Zulfiya Kayumovna (Pubmedia Social Sciences and Humanities, 2026)
This article evaluates the current state and effectiveness of the social protection system in Uzbekistan, focusing on its role in poverty reduction and welfare..The study analyzes government social assistance programs, the implementation of the "Social Register," and the mechanisms used to support vulnerable populations. The findings show that digitalization has significantly increased the transparency and accuracy of social aid distribution. However, the system still needs improvement in reaching rural populations. Strengthening social safety nets through integrated digital systems and targeted assistance is vital for long-term social stability and economic resilience in Uzbekistan.